Use of high-dose erythropoietin for repair after injury: A comparison of outcomes in heart and kidney - Glenda C Gobe; Christudas Morais; David A Vesey; David W Johnson (Society of Diabetic Nephropathy Prevention, 2013)
Context: There is a need to define the exact benefits and contraindications of use of high-dose recombinant human erythropoietin (EPO) for its non-hematopoietic function as a cytokine that enhances tissue repair after injury. This review compares the outcomes from use of EPO in the injured heart and kidney, two organs that are thought, traditionally, to have intrinsically-different repair mechanisms. Evidence Acquisitions: Directory of Open Access Journals (DOAJ), Google Scholar, Pubmed (NLM), LISTA (EBSCO) and Web of Science have been searched. Results: Ongoing work by us on EPO protection of ischemia-reperfusion-injured kidneys indicated, first, that EPO acutely enhanced kidney repair via anti-apoptotic, pro-regenerative mechanisms, and second, that EPO may promote chronic fibrosis in the long term. Work by others on the ischaemia-injured heart has also indicated that EPO promotes repair. Although myocardial infarcts are made up mostly of necrotic tissue, many publications state EPO is anti-apoptotic in the heart, as well as promoting healing via cell differentiation and stimulation of granulation tissue. In the case of the heart, promotion of fibrosis may be advantageous where an infarct has destroyed a zone of cardiomyocytes, but if EPO stimulates progressive fibrosis in the heart, this may promote cardiac failure. Conclusions: A major concern in relation to the use of EPO in a cytoprotective role is its stimulation of long-term inflammation and fibrosis. EPO usage for cytoprotection is undoubtedly advantageous, but it may need to be offset with an anti-inflammatory agent in some organs, like kidney and heart, where progression to chronic fibrosis after acute injury is often recorded.